Malacobdella arrokeana: Parasite or Commensal of the Giant Clam Panopea abbreviata? - Fernandez Alfaya, Jose Elias (2015)
We examined trophic relationship between the nemertean Malacobdella arrokeana and its host, the edible geoduck Panopea abbreviata by studying the diets of both species by direct (stomach contents) and indirect methods (stable-isotope analysis of C and N). In addition to these methods, the feeding behavior of M. arrokeana within the host and the morphology of its feeding organs were examined. The feeding behavior of M. arrokeana did not exhibit parasitic characteristics, and the proboscis morphology indicates it is unable to injure host tissues. Analysis of stomach contents revealed a diet consisting mainly of microalgae and diatoms. Panopea abbreviata and M. arrokeanashared similar trophic levels, presenting no differences in the spread of the isotopic niches and high overlap (SEAB overlapped 63%). Consistent with this, our results showed no differences in δδ15N or δδ13C values between the two species. The combination of direct and indirect approaches revealed that M. arrokeana has a diet similar to that of its host, confirming a commensal relationship.